2006
DOI: 10.1212/01.wnl.0000244485.51898.93
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal orbitofrontal development due to prematurity

Abstract: Premature birth affects cerebral gyrification, and this impairment is not reversible during childhood. Identification of the specific factors involved in abnormal brain maturation may lead to effective interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
61
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 35 publications
8
61
0
1
Order By: Relevance
“…Corpus callosum decrements have frequently been reported in very preterm subjects without PVL at different ages (34 -37), including with the use of VBM methodology (11,38). In agreement with Davatzikos et al (39), we found decrements in the corpus callosum in the group of PVL children group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Corpus callosum decrements have frequently been reported in very preterm subjects without PVL at different ages (34 -37), including with the use of VBM methodology (11,38). In agreement with Davatzikos et al (39), we found decrements in the corpus callosum in the group of PVL children group.…”
Section: Discussionsupporting
confidence: 92%
“…By using these procedures, we have previously found that premature adolescents without clinical WM lesions had WM reductions in several cortical and subcortical cerebral regions (11,12) and that prematures at low risk of neurodevelopmental disorders showed GM reductions, mainly involving the temporal lobe (13). However, this technique has yet to be used in the study of preterm children with PVL.…”
mentioning
confidence: 99%
“…WM deficits were seen symmetrically in the posterior part of the internal capsule and the superior, middle frontal, pre-and post-central gyri, and the optic radiation and unilaterally involving the left uncinate fasciculus. A recent preterm birth cohort of 50 adolescents showed diffuse regional WM volume decreases (18). Bilateral involvement of the superior and inferior longitudinal fasciculus was present.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, an association has been found between some of these abnormalities, such as delay in gyral development being highly related to the presence and severity of WM abnormalities (17). To date, WM volumetric studies in preterm infants and children have demonstrated total WM volume reduction to be significantly correlated with BW (11) and GA (12,18), and some studies further show the adverse effect of regional WM changes on neurocognitive function (19 -21).…”
mentioning
confidence: 99%
“…[19][20][21][22] In addition, several authors have commented on the regional vulnerability of the preterm brain, and studies of preterm individuals ranging from school age to young adulthood have reported both gray and white matter changes in the frontotemporal and hippocampal regions bilaterally. [23][24][25][26] The left temporal region is more markedly affected than the right, and preterm males are more likely to experience both decreases in volume and abnormalities of gyrification in the temporal lobes when compared with preterm females. 20,22,27 By contrast, Kesler et al reported disproportionately enlarged frontal gray matter in preterm children compared with term controls at 8 years of age.…”
Section: Volumetric Imaging and Microstructural Analysesmentioning
confidence: 99%